Evaluation of liquid culture for quantitation of Mycobacterium tuberculosis in murine models. - O'Sullivan, D; Sander, C; Shorten, R; Gillespie, S; Hill, A; McHugh, T; McShane, H; Tchilian, E (2007)
Quantitation of bacterial load in tissues is essential for experimental investigation of Mycobacterium tuberculosis infection and immunity. We have used an automated liquid culture system to determine the number of colony forming units (CFU) in murine tissues and compared the results to those obtained by conventional plating on Middlebrook agar. There is an overall good correlation between results obtained by the two methods. Although less consistency and more contamination was observed in the automated liquid culture, the method is more sensitive, less labour intensive and allows the processing of large numbers of samples.